Group movement in World of Warcraft Battlegrounds. (12th November 2010) - Miller, John L.; Crowcroft, Jon
Distributed Virtual Environment (DVE) topology management and message propagation schemes have been proposed for many years. Evaluating DVE message propagation schemes requires a variety of assumptions whose verity significantly affects results, such as details about avatar movement characteristics. We implemented two schemes for waypoint and hotspot detection, and examined their applicability for characterising avatar movement. We confirmed that waypoint detection does not yield good results for characterising human avatar movement, and gained new insight into why by rendering avatar movement as point clouds. We implemented an existing hotspot detection model, and proposed an enhancement to help overcome one limitation of cell-based hotspot detection. We were able to immediately apply this hotspot detection technique to help analyse group movement. We discovered that although a third of movement time in the battlegrounds is spent in inter-node journeys, less than a quarter of these journeys are made in groups.